VP28 interacts with PmRab7 irrespective of its nucleotide state - Patcha Sudsat; Jiraporn Srisala; Danaya Pakotiprapha; Satita Tapaneeyakorn; Kallaya Sritunyalucksana; Siripong Thitamadee; Sitthivut Charoensutthivarakul; Ornchuma Itsathitphaisarn (Scientific Reports)
Abstract In shrimp aquaculture, white spot syndrome virus (WSSV) infections severely impact production. Previous research highlighted the crucial role of the Penaeus monodon Rab7 (PmRab7) protein in WSSV entry, specifically its interaction with the viral envelope protein VP28. PmRab7 exists in two conformations: GDP-bound (inactive) and GTP-bound (active). This study, using ELISA and isothermal titration calorimetry (ITC), reveals that the PmRab7-VP28 interaction occurs irrespective of the nucleotide binding state of PmRab7. Comparing the binding affinity between VP28 and different PmRab7 conformations, including wild-type (WT, 22.5 nM), a fast nucleotide exchange (L129F, 128 nM), a GDP-bound form (T22N, 334 nM), and a favorably GTP-bound form (Q67L, 1990 nM), PmRab7-WT exhibits the strongest binding affinity, especially at a lower temperature (25 °C). The binding of PmRab7-WT and VP28 in the presence of excess nucleotide (WT with excess GDP, 924 nM, and WT with excess GTP, 826 nM) shows a 2-fold higher binding affinity than in the absence (WT, 1920 nM) indicating that the addition of excess nucleotide for PmRab7-WT enhanced the affinity for VP28. Together, these findings support the potential of PmRab7-WT as a promising therapeutic candidate for WSSV control in shrimp. Furthermore, from an industrial point of view, the ITC platform developed to study the VP28-PmRab7 interactions provides a high-throughput method for screening additives for shrimp feed that can inhibit this interaction.